(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Currently, the concept of "design" is much broader. Design has penetrated almost all areas of human activity. We buy newspapers, books and magazines, we pay attention to leaflets, labels and colorful posters, we encounter graphic design in print and on the Internet.